Environmental Impact Generated by the Solid Waste Dump in a hamlet of the city of Chota - López Chávez, Marina (2018)
The present investigation was converted for the purpose of, the environmental impacts that generate the tree of solid waste in an open sky in the Rambrán farmhouse, which receives the waste produced in the City of Chota; A descriptive and causal comparative study was carried out between July and December 2017, with a survey of the 120 inhabitants living in the hamlet in order to immerse themselves in the daily life of the community and have a clear perception of the dump. The Environmental Impact Assessment (EIA) was conducted through the Bidimensional Matrix, obtaining as a result, that the bad odors coming from the dump are causing respiratory diseases, likewise it is an attractive focus of flies, buzzards, rats, mosquitoes, affected factors such as soil, air, water, flora, fauna, landscape and quality of life of the people living in the area. The Environmental Impacts generated environmental factors for most of the environmental factors of their environment, have a negative rating and most of those that refer to most of the analyzed factors, a kind of contamination of soil, air, water, landscape , flora and fauna, reaching a negative impact of -333, which in some cases can be reversible if the form of treatment and final disposal of solid waste is changed.